Social Dimension of Taboo Language as Knowledge Power Analysis for Identifying Transferable Saying English Taboo in Internet - Sinarman Jaya; Ferri Susanto (PT. Islamic Research Publisher, 2022)
The research tries to describe how is the deepest knowledge about taboo, especially for social dimensions on the Internet; of course, it is as knowledge power Analysis for identifying transferable saying English Taboo in the internet and attempts to identify categories of English taboo words and to know them which the most dominant used by tweeps on their twitter. This research used an analysis of the document method systems. The populations of this research were 48 people. The samples of the research were 12 people. This research used simple random for sampling techniques. This research instrument was cheklist, which consists of five categories of taboo words based on Eschholz...The data were collected and analyzed by observing the time line of the twitter, copied or printed screen status that containt taboo words, classified taboo words based on Eschholz theory and categorized the functions of taboo words based on Lancker (1987). The research results showed that tweeps used 34 taboo words on their twitter in 105 statuses. The frequency of taboo words on the twitter were 178 times. The taboo words that tweeps used the most dominant on their twitter was “fuck”. In this research, there were five categories of taboo words used by tweeps on their twitter based on Eschholz sex and anatomy was the most dominant categories of taboo words. The tweeps used taboo words to show their anger, frustation, joy, and surprise.